2018
DOI: 10.1051/medsci/201834f111
|View full text |Cite
|
Sign up to set email alerts
|

miR-25 Promotes Melanoma Progression by regulating RNA binding motif protein 47

Abstract: Melanoma is the most aggressive skin cancer, and accounts for the major part of skin cancer-related deaths in the world. In addition, the underlying mechanism of tumor progression in melanoma remains far from being elucidated. In this study, we have evaluated the function of miR-25 in melanoma. First, we examined the expression of miR-25 in four melanoma cell lines (A875, MV3, M14 and uacc-257) and in a normal melanocyte cell line (HEM-a). Then, we overexpressed miR-25 in M14 cells. Our results show that miR-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The tumor suppressor gene miR-410 is downregulated in lung cancer tissues and induced apoptosis in lung cancer cells (22). miR-25 is downregulated in melanoma cells and promoted the progression of melanoma (23). In the present study, the potential roles of miR-96 in CRC were investigated.…”
Section: Discussionmentioning
confidence: 92%
“…The tumor suppressor gene miR-410 is downregulated in lung cancer tissues and induced apoptosis in lung cancer cells (22). miR-25 is downregulated in melanoma cells and promoted the progression of melanoma (23). In the present study, the potential roles of miR-96 in CRC were investigated.…”
Section: Discussionmentioning
confidence: 92%
“…Increasing evidence has identified the aberrant expression of miRNAs (microRNAs) in melanomagenesis including Uveal melanoma (UM) [114,115]. Jiang and Liu reported that miR-25 target the RNA-binding motif protein 47 (RBM47) and activated the PI3K/Akt/mTOR signaling pathway in melanoma cells [116]. Meng et al recently demonstrated clinically that miR-138 is significantly upregulated in malignant melanoma patients by regulating the PI3K/Akt/mTOR autophagy pathway via PDK1 dependent expression [117].…”
Section: Cutaneous Cancers Associated With Dysregulation Of the Pimentioning
confidence: 99%
“…Despite the presence of literature data on the role of miR-19b and miR-25 in melanoma cells [78][79][80] , their expression levels have not been previously analyzed in patient plasma. Therefore, for the first time, our data indicate that in metastatic melanoma patients the levels of miR-19b and miR-25 increase in stable and responding patients after one month of CPI therapy.…”
Section: Discussionmentioning
confidence: 99%